Alveolar epithelial TET2 is not involved in the development of bleomycin‐induced pulmonary fibrosis. Issue 5 (29th April 2021) - Qin, Wanhai; Crestani, Bruno; Spek, C. Arnold; Scicluna, Brendon P.; van der Poll, Tom; Duitman, JanWillem
Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic lung disease of unknown etiology with minimal treatment options. Repetitive alveolar epithelial injury has been suggested as one of the causative mechanisms of this disease. Type 2 alveolar epithelial cells (AEC2) play a crucial role during fibrosis by functioning as stem cells able to repair epithelial damage. The DNA demethylase Tet methylcytosine dioxygenase 2 (TET2) regulates the stemness of multiple types of stem cells, but whether it also affects the stemness of AEC2 during fibrosis remains elusive. To study the role of TET2 in AEC2 during fibrosis, we first determined TET2 protein levels in the lungs of IPF patients and compared TET2 expression in AEC2 of IPF patients and controls using publicly available data sets. Subsequently, pulmonary fibrosis was induced by the intranasal administration of bleomycin to wild‐type and AEC2‐specific TET2 knockout mice to determine the role of TET2 in vivo. Fibrosis was assessed by hydroxyproline analysis and fibrotic gene expression. Additionally, macrophage recruitment and activation, and epithelial injury were analyzed. TET2 protein levels and gene expression were downregulated in IPF lungs and AEC2, respectively. Bleomycin inoculation induced a robust fibrotic response as indicated by increased hydroxyproline levels and increased expression of pro‐fibrotic genes. Additionally, increased macrophage recruitment and both M1 and M2 activation were observed. None of these parameters were, however, affected by AEC2‐specific TET2 deficiency. TET2 expression is reduced in IPF, but the absence of TET2 in AEC2 cells does not affect the development of bleomycin‐induced pulmonary fibrosis.